Melanoma therapy with transdermal mitoxantrone cubic phases. (12th June 2016) - Yu, Xiang; Du, Lina; Zhu, Lifei; Liu, Xiaoyan; Zhang, Baolei; Fu, Guiying; Jin, Yiguang
Abstract: Context : Melanoma therapy absorbs attention because of the high morbidity and mortality. However, currently systematic administrations could take little therapeutic efficiency and severe side effects. Objective : An effective transdermal formulation for the convenient melanoma therapy was found and evaluated. Materials and methods : A mitoxantrone (MTO) cubic phase was prepared with glyceryl monooleate, ethanol and water. The permeation, cytotoxicity, in vivo anti-melanoma effect of the MTO cubic phases were evaluated. The anti-cancer mechanism of the MTO cubic phases was explored according to the immunohistochemistry and flow cytometry. Results and discussion : The isotropic structure of MTO cubic phases was identified. The transdermal permeability of MTO was greatly improved by the cubic phase compared to that of the MTO solution. The MTO cubic phases showed the high cytotoxicity in B16 melanoma cells evidenced by a modified electrical cell–substrate impedance sensing system. High anti-melanoma effect of the MTO cubic phases was confirmed according to the tumor volume changes and tumor weight. The tumor inhibitory rate of the MTO cubic phases was 68.44%. The calreticulin expression of B16 cells was improved by the MTO cubic phases, and the improved cell uptake of MTO was confirmed by the flow cytometry. Conclusion : The MTO cubic phase is a promising topical delivery system for melanoma therapy with the advantages of non-invasion and no severe side effects.